Virtual War - Skurzynski, Gloria (New York : Simon & Schuster Books for Young Readers, 1997)
In a future world where global contamination has necessitated limited human contact, three young people with unique genetically engineered abilities are teamed up to wage a war in virtual reality.
Keywords: Science fiction; Virtual reality